Features of the implantable medical products market - S. N. Pisaryuk (Вестник Северо-Кавказского федерального университета, 2023)
Today the market of medical devices is represented by a wide range of implantable products used in the field of traumatology and orthopedics. This segment is currently developing dynamically and is one of the most significant in the healthcare industry. The current situation in the joint replacement market favors the entry into the market and the strengthening of domestic manufacturers on it. The sanctions pressure both makes troubles and helps the domestic producer. Today we can already say that the technologies that have been developed and are being developed in our country in the field of joint replacement deserve attention: there are developments that allow increasing the service life of endoprostheses compared to imported analogues. The industry of endoprosthesis production in the Russian Federation is at the initial stage, there is an increase in projects requiring investment and the formation of production capacities. The state plays an important role, it should create favorable conditions for domestic producers, and thereby contribute to the process of import substitution. In this regard, it is advisable to investigate the current state of the joint replacement market in order to make a decision on the prospects of working on it, taking into account the assessment of the capacity and volume of the joint replacement market.